PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK KELAS III SD BERNUANSA DISCOVERY LEARNING - Asih Mardati; Hanum Hanifa Sukma (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
This research was conducted to produce class III Thematic learning tools with discovery learning nuances, as well as to see the level of quality of the LKPD, RPP, and Katar media were developed. This type of research includes Research and Development with the ADDIE development model which includes needs analysis, product design, product development, product implementation, and evaluation. Data collection techniques include the expert judgment of product feasibility and practitioner judgment. The data collection instrument included an expert judgment assessment sheet consisting of linguists, media, materials, and learning. The data analysis used was descriptive qualitative by converting the expert assessment score into the feasibility category. This research produces thematic learning tools consisting of LKPD, RPP, and Katar Media with a discovery learning approach to the theme of 3 objects around me for Class III SD. Based on the results of the assessment of the product developed, it is known that the results of the assessment from material experts obtained an empirical score of 75, learning experts obtained an empirical score of 69, media experts obtained an empirical score of 83 and linguists obtained a score of 63 with the criteria of the product category being good. Overall the products developed are in the good feasibility category